Influence of electromagnetic (EM) waves polarization modes on surface plasmon resonance - Murat N.F.; Mukhtar W.M.; Menon P.S.; Abdul Rashid A.R.; Ahmad Dasuki K.; Awangku Yussuf A.A.R. (EDP Sciences, 2024)
Indexed by Scopus